2021
DOI: 10.5530/ijopp.14.3.35
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Antibiotic Sensitivity Pattern in Children Hospitalized for Urinary Tract Infection in a Tertiary Care Hospital in South India

Abstract: Background:The etiology of urinary tract infection (UTI) and their antibiotic sensitivity pattern vary from time to time and across different areas in India. This study is designed to analyse the resistance of uropathogens to commonly used antibiotics. Aim: To study antibiotic resistance trends of uropathogens and assess the antimicrobial utilization pattern according to the antimicrobial susceptibility test in the paediatric department of a tertiary care hospital. Materials and Methods: It was an ambispective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…3m). In our study and after we mentioned all previous susceptibility tests results to 14 different antibiotics which commonly used in hospitals, shown us that a higher prevalence rate of resistance to commonly prescribed antibiotic agent, all the bacterial uropathogens showed [49] in India, by AbdulRazzaq (2013) [18] in Mosul, and by Mezal and coworkers (2011) [50] in Basrah. while this drugs exhibited low resistant rate in another study outside Iraq such as Jha and Bapat [51] reported that all the organisms causing UTI were sensitive to ciprofloxacin.…”
Section: Fig 3k Antimicrobial Susceptibility To Gentamycinsupporting
confidence: 55%
“…3m). In our study and after we mentioned all previous susceptibility tests results to 14 different antibiotics which commonly used in hospitals, shown us that a higher prevalence rate of resistance to commonly prescribed antibiotic agent, all the bacterial uropathogens showed [49] in India, by AbdulRazzaq (2013) [18] in Mosul, and by Mezal and coworkers (2011) [50] in Basrah. while this drugs exhibited low resistant rate in another study outside Iraq such as Jha and Bapat [51] reported that all the organisms causing UTI were sensitive to ciprofloxacin.…”
Section: Fig 3k Antimicrobial Susceptibility To Gentamycinsupporting
confidence: 55%